Consejo de publicación de la revista - Lozano, Alejandro; Saranz, Ricardo J. (Revista Methodo Investigación Aplicada a las Ciencias Biológicas, 2019)
Comité Editorial Dra. Jordana Auad Dr. Julio Bartoli Dra. Ana Bertoli Dr. Nicolás Crim Lic. Claudia Green Dr. Daniel Lerda Dra. Natàlia Lozano Dra. Vanina Marini Dr. Gustavo Molina Dra. Sara María Palacios Lic. Graciela Scruzzi Dr. Néstor Soria Dr. Ignacio Sosa Mgter.Jorgelina Ulloque Comité Editorial Nacional Dra. Beatriz Basso (CONICET-Mendoza, Argentina) Dr. Ricardo Juan Cabral (UNC-Córdoba, Argentina) Dr. Santiago Daniel Palma (UNC-Córdoba, Argentina) Dra. Dolores Román (UNC-Córdoba, Argentina) Dra. Edith Illescas (UM-CABA, Argentina) Dra. Irene Larripa (ANM-CABA, Argentina) Dr. Edgardo Moretti (CONICET-Mendoza, Argentina) Dra. Mariana Butinof (UNC- Córdoba, Argentina) Dra. Graciela Panzetta (CONICET-UNC, Córdoba, Argentina) Dra. Marina Ponzio (CONICET-UNC-Córdoba, Argentina) Comité Editorial Extranjero Dr. Adrián Gabriel Torres (Barcelona, España) Dr. Alejandro Urzua Moll (Santiago, Chile) Dr. Álvaro Cruz (Bahía, Brasil) Dr. Mario Calvo Gil (Valdivia, Chile) Dr. José Antonio Castro Rodríguez (Santiago, Chile) Dr. Víctor Patricio Díaz Narváez (Copiapó, Chile) Dr. Carmelo Escudero Díez (Madrid, España) Dra. María Dolores Paloma Ibáñez Sandin (Madrid, España) Dr. Pablo Zunino (Montevideo, Uruguay).